Potret Islam Tradisional â€œDayah dan Ulama di Aceh Abad Ke-20â€ dalam Perspektif Sejarah - Nuraini Nuraini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2014)
At the time of the Sultanate, dayah offers three levels of teaching (junior), rangkang, balee (senior) and dayah manyang (University). In some there were only junior dayah (rangkang) and senior (balee), whereas elsewhere found only university level course. Even so, in a certain place there are also three levels at once, ranging from junior to University. Before a pupil studying in Dayah, they've been able to read the Quran. The ability to read the Quran, they earn from home or from a teungku in meunasah. Information about very rare curriculum that can be obtained from historical background dayah; not a scholar was explaining about this Pada masa kesultanan, dayah menawarkan tiga tingkatan pengajaran, rangkang (junior), balee (senior) dan dayah manyang (universitas). Di beberapa dayah hanya terdapat junior (rangkang) dan senior (balee), sedangkan di tempat lain hanya ditemui tingkat universitas saja. Meskipun demikian, di tempat tertentu juga terdapat tiga tingkatan sekaligus, mulai dari junior sampai universitas. Sebelum murid belajar di Dayah, mereka sudah mampu membaca al-Quran. Kemampuan membaca Al-Quran tersebut, mereka dapatkan dari rumah atau dari seorang teungku di meunasah. Informasi tentang kurikulum sangat langka yang bisa didapatkan dari latar belakang sejarah dayah; tidak seorang sarjana pun yang menjelaskan tentang hal ini Kata Kunci: Dayah, Pendidikan Islam, Aceh.